ANALISIS PENDAFTARAN MEREK “MINYAK SEHAT” BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2016 - Varianto, Andy; Retnowulandari, Wahyuni (Tribuere, 2024)
A trademark serves as a distinguishing factor for goods and/or services produced by one company from those of similar companies. However, in practice, some trademarks contain elements that may mislead the public regarding the quality, benefits, or properties of the goods, potentially violating the provisions of Law Number 20 of 2016 concerning Trademarks and Geographical Indications. This study aims to analyze the regulations related to trademarks that cannot be registered under this legal framework and evaluate the registration procedure of the "Minyak Sehat" trademark, which was accepted despite allegations of containing misleading elements regarding the quality, benefits, or properties of the goods. This research employs a normative legal methodology with a descriptive approach and qualitative analysis. Based on the opinions of intellectual property experts, the "Minyak Sehat" trademark does not meet the criteria for registration as its meaning, both in isolation and in its entirety, violates several provisions of Article 20 of Law Number 20 of 2016. Furthermore, errors were identified in the registration process, particularly during the substantive examination phase.